Temperature and Substrate Effects on the Structural, Morphological, and Optical Properties of Iron Oxide Thin Films Prepared by Spray Pyrolysis Technique (Dhaka University Journal of Science, 2020)
Glass and Fluorine doped Tin Oxide (FTO) coated conducting glass substrates have been chosen for the deposition of Iron Oxide thin films prepared by Spray Pyrolysis Technique. The films were grown at different substrate temperatures (3500C, 4000C, and 4500C) and they were annealed at 3000C for 1 hr. Structural, morphological, optical characterizations of the films have been studied by X-ray diffraction, atomic force micrograph,UV spectroscopy methods. From the XRD studies, films on glass substrates are found to be amorphous in nature with α-hematite phase and crystalline on FTO coated conducting glass substrates. AFM analysis indicates that the films grown on glass substrates are rougher than the films on FTO coated conducting glass substrates. It reveals that the FTO coated conducting glass substrates can be a better choice as a substrate. The transmis sion spectra have been measured in the wavelength range 200-1200 nm. The transmittance of the films both on glass and FTO coated conducting glass substrates has been observed to be about 40- 80% in the wavelength range (500-1100) nm. The optical band gap energy values have been found to be in the range 2.10-2.37 eV.Dhaka Univ. J. Sci. 68(1): 79-85, 2020 (January)